A TRANSIT FORTRESS: DECONSTRUCTING THE LOGIC OF RISK IN CZECH REPUBLIC'S INTERNAL BORDER CONTROLS, 2020-2024 - Daffa Arifuddin Zakariya; Wishnu Mahendra Wiswayana (Intermestic: Journal of International Studies, 2025)
The free movement in the Schengen Area was gradually eroded by the reintroduction of Internal Border Controls (IBC), a trend currently being pursued not only by destination countries but also by transit countries such as the Czech Republic. Current literature largely employs securitization analysis with underlying existential threats, yet this approach fails to capture the logic underlying transit countries' policies. This paper aims to deconstruct the Czech Republic's IBC policy for 2020-2024, arguing that it is driven by a preventive logic of riskification. Through qualitative discourse analysis of government documents and secondary data, the study uncovers three aspects of riskification. First, the grammar justifies policies based on potential risks such as pandemics and the domino effect of migration pressure. Second, the locus of policy management of referential objects is not only migrants but also “what they carry” as evidenced by joint forces and random checks. Third, the performative effects of these policies create a new long-term border governance through intensive cooperation and joint patrols with neighbouring countries. This study demonstrates how risk management logic consistently erodes core principles of European integration, sacrificing for security measures to manage borders against future potential risks.